Det dansk-tyske ægyptologmøde i København 1941 - Pedersen, Lars Schreiber (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2024)
In August 1947 Copenhagen hosted the first international congress of Egyptologists since the end of the Second World War. About thirty leading Egyptologists from the United States, Africa and Europe (with the exception of Germany) made their way to the Congress, which had important issues on the agenda, including the creation of an International Union of Egyptologists and the re-establishment of the most important international journals whose activities had ceased during the war. The atmosphere among the participants was good, but there was a fly in the ointment. The Danish host of the Congress, Professor of Egyptology C.E. Sander-Hansen, had failed to invite the head of the Glyptotek’s Egyptian department, Otto Koefoed-Petersen. Koefoed-Petersen was far from happy with that decision, and he therefore launched attacks against Sander- Hansen in several Danish newspapers, in which he suggested that Sander-Hansen and other Danish members of the host committee had had links with representatives of the German occupying power during the war. Where Koefoed-Petersen got this information from is uncertain, but the information was true. In August-September 1941 a meeting of Danish and German Egyptologists took place in Copenhagen. The main reason for the meeting was to address the challenges faced by the long-standing collaboration between the scientific academies in Berlin and Copenhagen regarding the publication of the Dictionary of the Egyptian Language, Wörterbuch der ägyptischen Sprache. The outbreak of war in September 1939 had made this work difficult, as the dictionary’s extensive amount of source texts (Zetteln) and archive in Berlin had been taken to safety, while several of the dictionary’s younger employees had been called up for military service. The meeting in Copenhagen was attended on the German side by the professor of Egyptology at the University of Berlin, Hermann Grapow, who came to Denmark on 29 August 1941 in the company of the director of the Prussian Academy of Sciences in Berlin, the Orientalist Helmuth Scheel and the Berlin-based Danish Egyptologist Wolja Erichsen. During the first days in Copenhagen, Grapow and Scheel met with, among others, the president of the German Scientific Institute in Copenhagen (the Deutsche Wissenschaftliche Institut), which had opened in May 1941, the Kiel professor Otto Scheel, and with representatives from the German embassy. On 1 September the University of Copenhagen’s Egyptological laboratory in the heart of Copenhagen hosted the first meeting between the Danish Egyptologists and Hermann Grapow. The Danish side was represented by the Nestor of Danish Egyptology, H.O. Lange, and the younger Egyptologists C.E. Sander-Hansen, Aksel Volten and Wolja Erichsen. Three topics were on the agenda: continued collaboration on the Egyptian dictionary in Berlin, C.E. Sander-Hansen’s future work on the late Berlin professor Kurt Sethe’s comments on the oldest known religious texts from Egypt – the Pyramid Texts – and the plan to publish a demotic dictionary. Two days later Grapow gave a lecture at the German Scientific Institute, where Sander-Hansen and Volten were among the many prominent members of the audience, which also included several representatives from the German embassy, led by the plenipotentiary Cecil von Renthe-Fink. H.O. Lange had originally agreed to participate but later changed his mind, citing poor health and challenges navigating safely in the dark as reasons for his cancellation. On 6 September C.E. Sander-Hansen, Erik Iversen and Wolja Erichsen met with Scheel and Grapow at the German Scientific Institute. The meeting, which had come about at the initiative of the Danes, had a more informative nature and revolved around Lange’s impending eightieth birthday in October 1943 and the opportunity to publish a Festschrift in his honour. Grapow and Scheel also had a number of other tasks in Copenhagen. In addition to several meetings with the various representatives of the German occupying power in Denmark, Grapow held, among other things, a meeting about another ongoing German project regarding the registration and inventory of German medieval manuscripts in Denmark with the head of the Prussian Academy’s Deutsche Kommission manuscript archive, Hans Werner Pyritz, who had come to Copenhagen on 2 September, and with a German lecturer at the University of Copenhagen, Günther Jungbluth. Pyritz also had the opportunity to give a well-attended lecture at the German Scientific Institute before the small German delegation left Denmark again on 7 September 1941. Several German government institutions in both Copenhagen and Berlin subsequently considered the Danish-German Egyptologists’ meeting in Copenhagen a success. However, it was not, as had been hoped from the German side, the starting point for a more in-depth collaboration between the German Scientific Institute and Danish intellectuals. After the Danish-German meeting in Copenhagen, difficulties continued for the Egyptian dictionary’s remaining employees in Berlin, Grapow and Erichsen. Because of the war, otherwise completed works could not be printed, and in 1943 conditions in Berlin had become so uncertain for Wolja Erichsen and his family that they left the German capital and settled in Denmark. Erichsen never returned to the dictionary work in Berlin. The plans to publish a Festschrift to H.O. Lange came to nothing when, after a short illness, Lange passed away in January 1943. The German lecturer Günther Jungbluth had hardly got much further with his work of inventorying the German medieval manuscripts at the Royal Library and the University Library when he was called up for military service in January 1942 and had to leave Denmark. The Danish-German gathering in Copenhagen in 1941 had no consequences for the participating Danish Egyptologists after the liberation in May 1945. This was primarily due to the fact that the Danish public never found out about it – or rather, only did so very late. In 1941 the Danish newspapers wrote neither about the meeting of the Danish and German Egyptologists nor about Grapow’s and Pyritz’s lectures at the German Scientific Institute, with a number of German and Danish notables among the audience. The Danish-German meeting was therefore forgotten until Koefoed-Petersen brought it up in connection with the public dispute with Sander-Hansen in the late summer of 1947. Otto Koefoed-Petersen undoubtedly found the visit of his Danish Egyptologist colleagues to the German Scientific Institute during the occupation inappropriate. By bringing the subject up in connection with the Egyptologists’ conference in 1947, he probably hoped to be able to bring the Danish participants, and not least C.E. Sander-Hansen, into disrepute. However, that did not happen. Many newspapers were critical of Sander-Hansen’s actions regarding Koefoed-Petersen’s lack of invitation to the Egyptology conference, but none of them was apparently prompted to investigate the otherwise precarious subject of the comings and goings of Sander-Hansen and his colleagues at the German Scientific Institute during the occupation.